Transformation Based Digital Technology: The Effectivity of Psychosocial Intervention Method - Putra, I Kadek Agus Hendriawan; Ardhaneswari, Pande Putu Narisya; Ariasih, Ni Wayan Devi; Kanaya, I Komang Krisnata (UI Scholars Hub, 2022)
A multitude of patterns resulting from technological change have an influence on people's mental health. People in the digital era need strong mental health in order to prevent mental disease. Coupled with the pandemic condition that happened around two years ago, it also took a part of the economic chain stability in the public, which is really important for everyday daily life. From the literature studies that have been read, showed that approximately 20% of the Indonesian population has the potential to have a mental disorder. Based on the various mental health problems that occur, the approach using the psychosocial intervention method is a way that can be used as a solution. This study is literature review that Study efficacy of digital transformation method in psychological interview case, and research based on 48 journals from various online sources. The benefit of digital psychosocial intervention is saving cost for intervention time and making it easy for people to get intervention. This research aims to study how to use digital platforms as a means of solving psychosocial transformation. The result of this study found that digital psychosocial interventions have an efficacy that is given via several platforms.